Testosterone prohormone supplements - Brown, G. A.; Vukovich, M.; King, D. S. (Medicine & Science in Sports & Exercise, 2006)
Testosterone prohormones such as androstenedione, androstenediol, and dehydroepiandrosterone (DHEA) have been heavily marketed as testosterone-enhancing and muscle-building nutritional supplements for the past decade. Concerns over the safety of prohormone supplement use prompted the United States Food and Drug Administration to call for a ban on androstenedione sales, and Congress passed the Anabolic Steroid Control Act of 2004, which classifies androstenedione and 17 other steroids as controlled substances. As of January 2005, these substances cannot be sold without prescription. This article summarizes the current scientific knowledge regarding the efficacy and safety of prohormone supplementation in humans. The focus ist primary on androstenedione, but DHEA, androstenediol, 19-nor androstenedione, and 19-nor androstenediol supplements are also discussed. Contrary to marketing claims, research to date indicates that the use of prohormone nutritional supplements (DHEA, androstenedione, androstenediol, and other steroid hormone supplements) does not produce either anabolic or ergogenic effects in men. Moreover, the use of prohormone nutritional supplements may raise the risk for negative health consequences.